2012
DOI: 10.1187/cbe.11-09-0087
|View full text |Cite
|
Sign up to set email alerts
|

Are Africans, Europeans, and Asians Different “Races”? A Guided-Inquiry Lab for Introducing Undergraduate Students to Genetic Diversity and Preparing Them to Study Natural Selection

Abstract: Many students do not recognize that individual organisms within populations vary, and this may make it difficult for them to recognize the essential role variation plays in natural selection. Also, many students have weak scientific reasoning skills, and this makes it difficult for them to recognize misconceptions they might have. This paper describes a 2-h laboratory for college students that introduces them to genetic diversity and gives them practice using hypothetico-deductive reasoning. In brief, the lab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…An anonymous survey was composed of modified survey questions from assessments of another postsecondary science laboratory module (Kalinowski, 2012) and several questions developed by the authors that reflected the potential gains of teaching an issues-oriented science module (Lenz & Willcox, 2012). Closed-response survey questions used a rating system, as follows: 1 = Strongly Agree, 2 = Agree, 3 = Neither Agree Nor Disagree, 4 = Disagree, and 5 = Strongly Disagree.…”
Section: Survey Research On Laboratory Modulementioning
confidence: 99%
“…An anonymous survey was composed of modified survey questions from assessments of another postsecondary science laboratory module (Kalinowski, 2012) and several questions developed by the authors that reflected the potential gains of teaching an issues-oriented science module (Lenz & Willcox, 2012). Closed-response survey questions used a rating system, as follows: 1 = Strongly Agree, 2 = Agree, 3 = Neither Agree Nor Disagree, 4 = Disagree, and 5 = Strongly Disagree.…”
Section: Survey Research On Laboratory Modulementioning
confidence: 99%
“…Inquiry-based teaching practices place more responsibility for learning with learners; for example, students are responsible for decision making in experimentation ( Gormally et al ., 2011 , 2016), which may increase students’ interest in science ( Partin and Haney, 2012 ). We know that students in inquiry-based laboratory courses improve their skills with the scientific process ( Brickman et al ., 2009 ), science literacy ( Gehring and Eastman, 2008 ; Brickman et al ., 2009 ), conceptual knowledge ( Cox-Paulson et al ., 2012 ), and reasoning ( Beck and Blumer, 2012 ; Beck et al ., 2014 ; Kalinowski et al ., 2012 ). Additionally, a comparative study by Bilgin (2009) showed that students had more favorable attitudes toward inquiry-based learning when working in cooperative groups than when working alone.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on biological conceptions predominantly investigate the understanding of evolution and natural selection [ 14 19 ]. Conceptual studies on photosynthesis and related issues such as tree assimilation and wood synthesis date back to the 1980s, revealing one prominent alternative concept: Plants absorb nutrients from their environment [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%